How to Read and Determine the Specific Surface Area of Inorganic Materials using the Brunauer-Emmett-Teller (BET) Method - Irwansyah, Ferli Septi; Amal, Alfi Ikhlasul; Diyanthi, Erlinda Widyasmara; Hadisantoso, Eko Prabowo; Noviyanti, Atiek Rostika; Eddy, Diana Rakhmawaty; Risdiana, Risdiana (ASEAN Journal of Science and Engineering, 2024)
The specific surface area of inorganic materials is a crucial parameter that influences their performance in various applications. The Brunauer-Emmett-Teller (BET) method is widely used for accurately determining the surface area of porous materials. This study presents a comprehensive guide to determining the specific surface area of inorganic materials using the BET method. The paper outlines the theoretical background of the BET method, the experimental procedures involved, and the data analysis techniques. Additionally, we discuss the limitations and potential sources of errors in the BET method. The proposed guide aims to provide researchers and practitioners with a systematic approach to accurately measure the specific surface area of inorganic materials, enabling informed decision-making and enhancing material design and optimization processes.